MODEL DAN STRATEGI PEMBELAJARAN TEMATIK UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA - MUBAROK, MUSLIM (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The main focus in thematic learning is on student understanding and the development of relevant skills along with understanding the concept. The article also discusses the importance of distinguishing between teaching and learning, where teaching refers to the teacher's efforts in facilitating the achievement of students' learning goals, while learning highlights the interactions between teachers and students. There are three main models in thematic learning: Connection Model, Spider Web Model, and Integration Model, each of which has advantages and disadvantages in integrating subjects. The Spider Web Model adopts a thematic approach by using themes as a link between subjects. The Integration Model seeks to create connections between concepts, skills, topics, ideas, and activities within a particular field of study, but requires greater collaboration between teachers and a mature curriculum. The Connectedness Model, basically, creates connections between concepts, skills, topics, ideas and activities in a particular field of study by utilizing themes as a link. ABSTRAKFokus utama dalam pembelajaran tematik adalah overpada pemahaman siswa dan perkembangan keterampilan yang relevan seiring dengan pemahaman konsep tersebut. Artikel juga membahas pentingnya membedakan antara pengajaran dan pembelajaran, di mana pengajaran merujuk pada upaya guru dalam memfasilitasi pencapaian tujuan pembelajaran siswa, sementara pembelajaran menyoroti interaksi antara guru dan siswa. Terdapat tiga model utama dalam pembelajaran tematik: Model Keterhubungan, Model Jaring Laba-laba, dan Model Keterpaduan, yang masing-masing memiliki kelebihan dan kekurangan dalam mengintegrasikan mata pelajaran. Model Jaring Laba-laba mengadopsi pendekatan tematik dengan menggunakan tema sebagai pengikat antara mata pelajaran. Model Keterpaduan berusaha menciptakan keterhubungan antara konsep, keterampilan, topik, ide, dan kegiatan dalam satu bidang studi tertentu, namun memerlukan kolaborasi yang lebih besar antara guru dan kurikulum yang matang. Model Keterhubungan, pada dasarnya, menciptakan keterkaitan antara konsep, keterampilan, topik, ide, dan kegiatan dalam satu bidang studi tertentu dengan memanfaatkan tema sebagai penghubung.